Pencegahan Pernikahan Usia Dini Melalui Program Pusat Informasi dan Konseling Remaja (PIK-R) di Dinas Pengendalian Penduduk dan Keluarga Berencana Kabupaten Karawang: Prevention of Early Marriage through the Adolescent Information and Counseling Center (PIK-R) Program at the Karawang Regency Population Control and Family Planning Office - Rachmat Ramdani; Cucu Sugiarti; Rizzka Aulia Anggriani (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2023)
This research highlights the concept of preventing early marriage through the Adolescent Information and Counseling Center (PIK-R) program at the Karawang Regency Population Control and Family Planning Office. This research uses qualitative research methods with case study design and data analysis using the Miles and Huberman model. The theory that researchers use in this study is the prevention of early marriage according to Noorkasiani, et al (Ulfah, 2018). Based on the findings in the field, the four dimensions have not gone well. First, in the dimension of directing adolescents who are not married, it was found that there was no formation of the PIK-R group and the absence of supporting facilities and infrastructure. Second, the education dimension of adolescents who are married was found that adolescents who are married have not received PAP (First Child Delay) education from ppkb Pedes and KUA districts and lack of budget to implement the PAP program. Third, regarding the dimension of counseling families who have adolescents, the findings of researchers in the field, namely the establishment of Adolescent Family Development (BKR) in Pedes District have not been evenly distributed and there are only two groups that get a District Decree and the absence of regeneration of BKR members which causes the education provided unevenly to other communities. Fourth, namely in the dimension of socialization of young marriage culture, it was found that there was no socialization provided by related agencies that socialize the culture of marrying young in society so that the culture of marrying young would continue to develop. The non-running of these four dimensions in preventing early marriage causes the spread of reproductive education and early marriage to adolescents not to run. So that this is one of the factors causing free behavior in adolescents who end up in early marriage.